ISOLASI DAN EKSTRAKSI DAUN KALIANDRA (Calliandra calothyrsus) SEBAGAI KONSENTRAT PROTEIN DAUN DITINJAU DARI TITIK ISOELEKTRIK, ASAM AMINO DAN ZAT ANTINUTRISI - Imam Wahyudi; Efka Aris Rimbawanto (ANGON: Journal of Animal Science and Technology, 2022)
Background. Research "Isolation and Extraction of Calliandra (Calliandra calothyrsus) Leaf as Leaf Protein Concentrate Judging from Isoelectric Point, Amino Acids and Antinutrients". This study aims to determine the isoelectric point, total amino acid content and the content of antinutrient tannins in the protein concentrate of calliandra leaves extracted and isolated from the protein. Materials and Methods. The research material used was calliandra (Calliandra calothyrsus) leaves. Determination of the isoelectric point using the modified Yatno method (2009), the total amino acid content using the high-performance liquid chromatography (HPLC) method, crude protein analysis using the Kjedhal according to AOAC (2005), and the content of antinutrient tannins using the butanol-HCl method. Results. The results showed that the isoelectric point of the calliandra leaf protein concentrate was reached in the first extraction with 0.05 N NaOH and pH 8 phosphate buffer in the second extraction resulting in 7.2 mg/ml protein precipitate with a crude protein content of 48.94%. The amino acid composition of calliandra leaf protein concentrate was higher than that of soybean meal except for glutamine. Conclusion. The tannin content produced in this study was 0.01% so that the calliandra leaf protein concentrate was safe to use as a protein source in poultry rations.